Plasminogen activator inhibitor is significantly elevated in liver transplant recipients with decompensated NASH cirrhosis - Dmitri Bezinover; Gloriany Rivas; Breianna Hummer-Bair; Zakiyah Kadry; Jonathan Stine (BMJ Open Gastroenterology)
Background Non-alcoholic fatty liver disease is a prohaemostatic state with abnormal primary, secondary and tertiary haemostasis. Plasminogen activator inhibitor (PAI)-1 is the best-established marker for prohaemostasis in non-alcoholic fatty liver disease. While epidemiological studies demonstrate decompensated non-alcoholic steatohepatitis (NASH) cirrhosis patients have increased rates of venous thromboembolism, including portal vein thrombosis, mechanistic studies have focused exclusively on patients without or with compensated cirrhosis. We aimed to characterizecharacterise PAI-1 levels in decompensated NASH cirrhosis.Methods PAI-1 level was measured in consecutive adult liver transplant recipients immediately prior to liver transplantation. Multivariable models were constructed using linear regression to assess factors related to PAI-1 level.Results Forty-six subjects with mean age 57 (IQR 53–62) years and Model for Endstage Liver Disease (MELD) score of 34 (IQR 30–40) were enrolled. Baseline characteristics were similar between NASH (n=10) and non-NASH (n=36) subjects except for rates of diabetes and hyperlipidaemia. Mean PAI-1 level was greater in NASH (53.9, 95% CI 33.3 to 74.5 mg/mL) when compared with non-NASH (36.1, 95% CI 28.7 to 43.5), p=0.040. NASH remained independently predictive of PAI-1 level prior to transplant on adjusted multivariable modelling (β 40.13, 95% CI 14.41 to 65.86, p=0.003). Conclusions: PAI-1 level is significantly elevated in decompensated NASH cirrhosis independent of other pro-haemostatic factors. This may explain the greater rates of venous thromboembolism in decompensated NASH cirrhosis. Future study focusing on prevention of venous thromboembolism in this population is paramount to improve patient-oriented outcomes given the high morbidity and mortality of venous thromboembolism and the significant impact it has on transplant candidacy.